2020
DOI: 10.1371/journal.pone.0235413
|View full text |Cite
|
Sign up to set email alerts
|

RNA from stabilized whole blood enables more comprehensive immune gene expression profiling compared to RNA from peripheral blood mononuclear cells

Abstract: Monitoring changes in the immune profile in blood samples can help identifying changes in tumor biology and therapy responsiveness over time. Immune-related gene expression profiles offer a highly reproducible method to monitor changes of the immune system. However, measuring gene expression profiles in whole blood samples can be complicated because of the high protein and enzyme abundancy that affect the stability and quality of the RNA. Peripheral blood mononuclear cells (PBMCs) are one the most commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…With bulk RNA-seq, evaluating the expression of immune-related genes and enrichment of immune-related pathways can reveal the inflammatory state of the TIME ( 29 , 90 ). A possible, and promising, solution is to perform RNA-seq on immune cells found in blood or CSF, which could be correlated to the TIME ( 93 , 156 ). Although, to our knowledge, no such experiments have been performed to monitor pediatric CNS malignancies yet, studies on other cancers have shown the potential of using these more readily accessible biomaterials to monitor the anti-tumor immune response during therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With bulk RNA-seq, evaluating the expression of immune-related genes and enrichment of immune-related pathways can reveal the inflammatory state of the TIME ( 29 , 90 ). A possible, and promising, solution is to perform RNA-seq on immune cells found in blood or CSF, which could be correlated to the TIME ( 93 , 156 ). Although, to our knowledge, no such experiments have been performed to monitor pediatric CNS malignancies yet, studies on other cancers have shown the potential of using these more readily accessible biomaterials to monitor the anti-tumor immune response during therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although, to our knowledge, no such experiments have been performed to monitor pediatric CNS malignancies yet, studies on other cancers have shown the potential of using these more readily accessible biomaterials to monitor the anti-tumor immune response during therapy. For example, circulating miRNA levels were found to be correlated to the absolute neutrophil count in pancreatic cancer ( 93 ). Moreover, comparing immune signatures of patients who respond to those who do not respond to a particular type of therapy can eventually guide therapy decision ( 157 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of immune response-related genes was analyzed using an nCounter Analysis System with a PanCancer Immune Profiling Panel (NanoString Technologies, Seattle, WA, USA) (8). This panel consists of 730 immune response-related genes, covering 24 different immune cell types, and both the adaptive and innate immune responses (14). Analysis was performed as reported previously (9,(14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
“…Blood sample processing and isolation of PBMC prior to analysis affects gene regulation within hours and may affect miR transcription even more rapidly [94][95][96]. In contrast, our approach allowed us to create a direct snap shot of the transcriptomic state, since all cells were immediately lysed and total RNA was stabilized [97]. However, several limitations must be addressed.…”
Section: Limitationsmentioning
confidence: 99%